PENERAPAN METODE HUNGARIAN DALAM OPTIMALISASI ALOKASI SUPIR EKSPEDISI SEBAGAI STRATEGI PENINGKATAN EFISIENSI WAKTU DISTRIBUSI PADA CV SEKAWAN BANDUNG - Aprian Maulana; Hadist Guida Herdiana; Wildan Sami Kalamullah; Somadi Somadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
CV Sekawan Bandung is an enterprise operating in the freight forwarding and goods distribution sector. Currently, the allocation of driver tasks at the company does not consider route travel-time efficiency, resulting in inefficient distribution processes and customer complaints. This study aims to determine the most effective task assignment by applying a descriptive quantitative approach using the Hungarian Method. Data were collected through observation and interviews. The results indicate a minimum total time of 946 minutes, with the following task allocation: Wahyu on the Cirebon route (238 minutes), Dedi on the Cianjur route (110 minutes), Edi on the Tasik route (186 minutes), and Deden on the Purwokerto route (412 minutes). These findings demonstrate that the method enables more accurate job placement, thereby enhancing distribution efficiency and supporting CV Sekawan Bandung's operational performance.